Transgender and Nonbinary Experiences of Victimization in Health care - Kattari, Shanna K. (Journal of interpersonal violence, 2021)
Transgender and nonbinary (TNB) individuals experience high rates of myriad types of victimization, including in health care settings. Many TNB people avoid medical visits for fear of mistreatment and, when they do visit a provider, report negative experiences (e.g., denial of services, misgendering, verbal abuse). These negative experiences are heightened for TNB individuals who have an intersecting marginalized identity (e.g., low socioeconomic status, disability). Using data from the 2015 United States Transgender Survey, the largest survey of TNB individuals in the United States to date, the present study examines differential experiences of victimization in health care settings by TNB identity and other demographics (i.e., race, age, class, educational level, disability). A series of multivariate logistic regressions were run to determine adjusted odds ratios (AORs) for TNB individuals recently (i.e., in the past year) experiencing four forms of victimization: (a) doctor/health care provider used harsh or abusive language; (b) doctor/health care provider was physically rough or abusive; (c) patient was verbally harassed in health care setting; and (d) patient experienced unwanted sexual contact in health care setting. Frequency of victimization varied by gender identity and type of victimization; the most prevalent form was verbal harassment by a doctor/provider (5.84%) and the least prevalent was unwanted sexual contact in a health care setting (1.20%). Although findings varied by form of violence, generally, regression models demonstrated elevated odds of experiencing some form of health care victimization for those who were transgender compared with genderqueer, biracial/multiracial compared with White, low income compared with higher income, and disabled compared to non-disabled. In addition, odds ratios for victimization increased with age and, for some forms, increased with low educational attainment. We discuss the need for increased mandatory trainings for providers to reduce discriminatory and violent behavior toward TNB patients, as well as intersectional research to better ascertain the extent and nuance of victimization within TNB health care.